Design of the Control Device for Metro Train Traction Energy Consumption Test - SUN Zeyong; ZHOU Yuan; YIN Yuan (Kongzhi Yu Xinxi Jishu)
Excessive total traction power consumption of metro train is a major problem faced by metro operation companies. In order to quantitatively evaluate traction energy consumption of subway trains, promote manufacturers to continuously optimize the design of traction system and reduce traction energy consumption of metro trains, this paper comprehensively analyzes the factors that affect energy consumption of subway trains, according to the vehicle control demand of traction energy consumption test of metro trains, a portable control device for traction energy consumption test is designed according to the requirements. Automatic operation of metro trains of different manufacturers is realized by simulating level signal of driver controller. Traction energy consumption data of metro trains is simultaneously collected and analyzed. Test result shows that the device can ensure that the maximum speed error of the trains which running according to the planned curves during the test is less than 2 km/h, solve the problems of inconsistent operation process and unreliable test data caused by manual operation of trains, and can meet the vehicle control requirements for traction energy consumption test of metro trains from different manufacturers.